Marketing 4.0 In The Era Of Online Digitalization - Sabilar Rosyad; Anim Fattach (Sean Institute, 2025)
In the current era this, the introduction concepts such as big data, social media, responsibility answer social companies, and e-commerce have No off become part from life this, then transition to Marketing 4.0 increasingly fast. One of the activity the most important thing that influences decision purchase consumer is e-commerce. E-commerce plays a role decisive role in stages and purchasing process. For reason This, e-commerce has become issues that increase interest individual in process and decision purchase every day and need emphasized. In line with all that, the concept of digital marketing and e-commerce will handled in broad framework in study this. In addition, the digitalization of e-commerce sites will held in review literature on the side environment and techniques that can used in scope digital marketing. Approaches and trends new guide modern marketing is changing from day to day. The most important reason change This based on rapid transformation in technology information and communication. For reason this is important for manager marketing For adapt with transformation this and using media and techniques in digital marketing.